USE OF DIGITAL EDUCATIONAL TECHNOLOGIES IN TEACHING INFORMATICS - M. X. Xalmetova (Galaxy International Interdisciplinary Research Journal, 2022)
The use of digital technologies in various fields of education today is one of the most important trends in the educational process in the world. Such technologies allow making the learning process better and more interesting because by using media and interactive tools the teacher can interest students by implementing different methods of classroom work: the method of projects, research, developmental educational games, and more. That is why the article considers the possibilities of using various digital educational resources in teaching computer science to primary school students. Examples of using Google cloud services (Google Docs, Google Sheet, Google Classroom, YouTube, Google Knol, Google Site, etc.), cloud-based learning management systems (because LMS has all the basic functionality that scientists relate to the educational environment of the educational institution), cloud-based smart card creation services, mass open online courses (because they provide the opportunity to create and maintain a forum of registered users, where students can communicate and get answers to their questions from teachers or more competent users of IOC), specialized tools for teaching computer science: online compilers, automated systems for checking programming tasks (ALGOTESTER, NetOI Olympiad, e-olymp Internet portal, because with their help students have the opportunity to solve problems and prepare for classes, as well as check their solutions without the help of a teacher, compare the level of their skills with thelevel of other users, which, in turn, stimulates the increase of knowledge in this field and promotes the development of self-esteem), games for learning programming languages(CodeMonkey, CodeCombat, CODINGAME). It is established that in the process of the digital transformation of the learning process there is an active interest of students, as there are relevance and novelty of content, clarity, disclosure of knowledge, game technology, practical research, and problem-based learning